Random walk and reserves modeling in studying pensions funds sustainability - Ferreira, M. A. M. (Proceedings of the International Scientific Conference. Quantitative Methods in Economics. Multiple Criteria Decision Making XXI, 2022)
Random walk is a stochastic process classic example, used to study a set of phenomena and, particularly, as in this article, models of reserves evolution. Random walks also allow the construction of significant complex systems and are also used as an instrument of analysis, being used in the sense of giving a theoretical characteristic to other types of systems. Our goal is primarily to study reserves to see how to ensure that pension funds are sustainable. This classic approach to the pension funds study makes it possible to draw interesting conclusions about the problem of reserves.